Parental Response to Only Children: Breaking the Stereotypes - Levy, Rona L. (Children (Basel), 2021)
While much has been written about the relationship between only child status and parents’ behavior toward children, and consequent personality and intelligence, little is known about the relationship between only child status, parental response to illness, and subsequent child illness behavior. In this study, 227 mothers of 342 children completed measures designed to assess: (a) their children’s school attendance, (b) their own psychological status, and (c) their own responses to their children’s expressions of stomach pain. Parents of only children were more likely to minimize their children’s gastrointestinal symptoms than were parents of children with at least one sibling. In addition, only children were less likely to miss school. Parental protectiveness did not differ as a function of only child status. These findings are somewhat discrepant with commonly held beliefs about parents’ patterns of responding to only children.